Fabrication of iron-nickel alloy microcomponents by centrifuge-assisted micromolding. Issue 5 (February 2016) - Zhou, Han; Su, Bo; Guo, Tieming; Meng, Junhu
Abstract Iron-nickel alloys exhibit lots of attractive properties, such as magnetic and conductivity properties, as well as excellent corrosion resistance. These properties make them suitable for making microcomponents. This paper presents the fabrication of iron-nickel alloy microcomponents (microchannel, microwell, micromixer, and microgear) from an ethanol-based composite slurry by centrifuge-assisted micromolding. Polydimethylsiloxane (PDMS) molds were replicated from microstructured silicon masters. A stable ethanol-based iron-nickel composite slurry with a high solid content of 85 wt% was prepared and filled into the PDMS molds by the aid of centrifugation. After drying, green microcomponents were demolded and followed by sintering in hydrogen atmosphere. Sintering profile was established by TGA. The green and sintered microcomponents had good shape retention and were free of cracks. The highest density of the microcomponents (97.3 RD%) was achieved at 1070 °C; the corresponding microhardness and Young's modulus were 167.8 HV and 175.4 GPa, respectively. The linear shrinkage increased with sintering temperature and the maximum value was about 12.5 %.